Latin American “left drift” is set to the right (some ﬁnishing touches to the “portrait” of the “right turn”) - Liudmila Okuneva (Ибероамериканские тетради)
The article deals with the reﬂections on the concept of the “right” and the “left” in Latin America, on the causes and characteristics of the completion of the “leftist cycle” and the advent of the “right turn”.